Determinants of house improvements in selected suburban residential subdivisions - Vicente Abe A. Relleve (Quezon City College of Architecture, University of the Philippines Diliman, 2006)
This is a three-year study of suburban subdivisions. In the final year of the study, it uncovered the determinants involved in the various improvements made by the homeowners to their housing units located in the two suburban subdivisions, namely, Palmera Hills I and Palmera Hills VI in Taytay, Rizal. Thorugh formal surveys of active member of the homeowner's associations, coupled with follow-up interviews, personal observations and supplementary readings, the study documented peculiar characteristics of these two subdivisions, the quality of housing units originally provided by the developer, the corresponding improvements that were introduced by the homeowners after acquiring the units, the types of improvements, reasons, cost and financing, year of execution, future plans for improvements and the collective effects of such improvements in the entire development. From these gathered data, the proponent deduced the underlying determinants which can serve as reference for prospective homeowners or insights and design tools for designers, planners and developers of similar residential subdivision projects.
Thesis (Master of Architecture : Housing)--University of the Philippines, Diliman
Keywords: Dwellings -- Remodelling; Housing development